Implementasi Metode Group Investigation untuk Meningkatkan Hasil Belajar Kelas VI SDN Mejayan 01 pada Materi Lestarikan Hewan dan Tumbuhan - Mariyono Mariyono (UNIVERSITAS PGRI MADIUN, 2022)
In the implementation of teaching and learning activities in the classroom there are weaknesses in the learning process, including the lack of optimal student involvement in learning so that it is passive. Teacher-centered learning activities, as a result students are more likely to listen, record and memorize. Students cannot find their own knowledge and skills. Therefore it is necessary to improve learning methods. This study aims to determine the implementation of the Group Investigation (GI) to improve learning outcomes and the activity of class VI students at SDN Mejayan 01. This research was carried out at SDN Mejayan 01, Mejayan District in two cycles consisting of cycle I and cycle II. This research approach is qualitative and quantitative. Data collection techniques using tests and observation sheets.The results showed that the application of the Group Investigation method could improve the learning outcomes of class VI students at SDN Mejayan 01 with the percentage of classical completeness increasing from 44% to 93%. The application of the Group Investigation learning method can increase the activity of class VI students at SDN Mejayan 01 with a classical percentage of activity from 67% to 100%.